Metronidazole in a single dose for the treatment of trichomoniasis. Failure of a 1-g single dose. - Austin, T W (1982)
To determine the minimum effective dose of metronidazole in the treatment of vaginal trichomoniasis, a randomised clinical trial comparing single 1-g and 2-g doses was carried out on 163 patients attending sexually transmitted diseases and family planning clinics. Seventy-two of 86 (84%) patients receiving a single 2-g dose of metronidazole were cured compared with only 42 of 77 (55%) receiving a 1-g dose. The body weight of the patient was a significant variable affecting treatment outcome only in the latter group; 69% of patients weighing more than 57 kg or less when cured compared with only 43% of those weighing more. Patients who failed after either dose regimen were retreated with a single 2-g dose. Eighteen of 21 (86%) and seven of 10 (70%) failures with the initial 1-g and 2-g doses respectively were cured. A single 1-g dose of metronidazole is not recommended as routine treatment for vaginal trichomoniasis.